PENGARUH MODAL, KUALITAS ASET, DAN EFISIENSI TERHADAP HASIL PENGEMBALIAN PADA BANK PEMBIAYAAN RAKYAT SYARIAH DI BAWAH PENGAWASAN BANK INDONESIA PURWOKERTO - Lina Krisnawati (JBIMA (Jurnal Bisnis dan Manajemen), 2014)
This study aimed to examine the effect of the Capital, Asset Quality, and Efficiency of the Results Return on BPRS 2008-2010. The data used in this study was obtained from the Financial Report BPRS issued by Bank Indonesia. After passing through the stage purposive sample, the samples are fit for use 6 banks. Data analysis techniques in this study using multiple regression analysis. F test showed that the variables of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), and ROA jointly affect significantly the profitability variable. While partially by t test, showed that the variables of the Capital Adequacy Ratio (CAR) and Non-Performing Financing (NPF) that has positive effect was not significant, and the variable ROA has a significant negative effect. The results also show the adjusted R2 value of 37, 6%. The results of this study can be taken into consideration for calculating the profitability of the bank management.